Hubungan Faktor Ekonomi dan Latar Belakang Sosial Terhadap Keputusan Masyarakat Melakukan Pemeriksaan Preventif Kesehatan Gigi Di Wilayah DKI Jakarta - Meitarilia Yuan Istidaniah; Rudi Purwono; Ni Made Sukartini; Wahyu Aditama Putra Mukti Wibawa (Universitas Madura, 2025)
Oral health is an integral part of overall well-being and significantly impacts quality of life. However, awareness of preventive dental check-ups remains low in many countries, including Indonesia. This study aims to analyze the economic and social determinants influencing individuals' decisions to undergo preventive dental check-ups in Jakarta. A cross-sectional survey design was used, collecting data from selected respondents through structured questionnaires. Independent variables included economic factors (income, health insurance) and social background (age, education level), while the dependent variable was the frequency of preventive dental check-ups. Data analysis employed descriptive statistics and logistic regression. Simultaneous testing reveals that the examined variables influence dental visits (Prob > Chi² = 0.0213) with a low contribution (Pseudo R² = 0.0287), suggesting that economic and demographic factors play a minor role in decision-making. These results highlight the need for health policies that go beyond financial and demographic considerations. Strategies such as raising awareness of the importance of preventive dental care are essential to increasing public access and adherence to oral health practices. This research provides insights for policymakers to design more effective and inclusive health interventions aimed at reducing dental disease prevalence and improving public health, particularly in Jakarta.